2022
DOI: 10.3390/genes13111921
|View full text |Cite
|
Sign up to set email alerts
|

POLDIP3: At the Crossroad of RNA and DNA Metabolism

Abstract: POLDIP3 was initially identified as a DNA polymerase delta (Pol δ) interacting protein almost twenty years ago. Intriguingly, it also interacts with proteins involved in a variety of RNA related biological processes, such as transcription, pre-mRNA splicing, mRNA export, and translation. Studies in recent years revealed that POLDIP3 also plays critical roles in disassembling genome wide R-loop formation and activating the DNA damage checkpoint in vivo. Here, we review the functions of POLDIP3 in various RNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Despite the demonstration being conducted in cycling cells, SIRT1 implication in the NHEJ DDR pathways could also be effective in cells post-mitotically, and it could be linked to its protective roles in several neurodegenerative diseases, including Alzheimer’s, Parkinson’s, and ALS [ 104 ]. On the other hand, POLDIP3 plays critical roles in disassembling R-loops genome-wide and activating the DNA damage checkpoint [ 105 ], and its transcript is one of the well-characterized TDP-43 targets. In particular, inclusion of POLDIP3 exon 3 was significantly altered in different cell lines depleted for TDP-43 and other hnRNPs linked to TDP-43 functions [ 59 , 77 , 78 ], as well as in various motor regions of CNS of ALS patients [ 106 ].…”
Section: Tdp-43 Role In Chromatin Remodeling and Transcriptionmentioning
confidence: 99%
“…Despite the demonstration being conducted in cycling cells, SIRT1 implication in the NHEJ DDR pathways could also be effective in cells post-mitotically, and it could be linked to its protective roles in several neurodegenerative diseases, including Alzheimer’s, Parkinson’s, and ALS [ 104 ]. On the other hand, POLDIP3 plays critical roles in disassembling R-loops genome-wide and activating the DNA damage checkpoint [ 105 ], and its transcript is one of the well-characterized TDP-43 targets. In particular, inclusion of POLDIP3 exon 3 was significantly altered in different cell lines depleted for TDP-43 and other hnRNPs linked to TDP-43 functions [ 59 , 77 , 78 ], as well as in various motor regions of CNS of ALS patients [ 106 ].…”
Section: Tdp-43 Role In Chromatin Remodeling and Transcriptionmentioning
confidence: 99%
“…Subsequently, the Lee lab demonstrated that POLDIP3 has a critical role in regulating the enzymatic activity of DNA polymerase δ [ 4 ]. In a review article, Singh and colleagues discuss the biochemical and biological functions of POLDIP3, not only in the context of DNA metabolism, but also its role in various RNA metabolic pathways [ 12 ]. In partnering with DNA polymerase δ, the flap endonuclease 1 (FEN1) has a significant function in Okazaki fragment maturation [ 5 ] and in processing DNA–RNA hybrids, i.e., R-loops [ 13 ].…”
mentioning
confidence: 99%
“…In a review article, Barnes and colleagues discussed the molecular mechanism of MiDAS in the context of telomeres [ 19 ]. Additionally, since both POLDIP3 and BIR have been implicated in the ALT pathway, the two articles written by Singh et al and Riders et al are valuable resources to further the understanding of the ALT pathway [ 10 , 12 ]. Finally, Batista and colleagues summarized the biology and therapeutics of Hutchinson-Gilford Progeria Syndrome (HGPS), one of the premature aging syndromes [ 20 ].…”
mentioning
confidence: 99%